Social autopsy analysis of the determinants of neonatal and under-five mortalities in Nigeria, 2013-2018 - Robinson D Wammanda; John Quinley; George I Eluwa; Adeyinka Odejimi; Michael Kunnuji; William Weiss; Inuwa B Jalingo; Olorunimbe T Ayokunle; Alice R Nte; Rebekah King; Ana C Franca-Koh (Journal of Global Health Reports)
# Background